(untitled) - Kirst-Ashman, Karen Kay (Belmont, Calif., 2008)
Includes bibliographical references (p. 387-405) and index (p. 406-414); Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social ecology; Social psychology; Human behavior; Communities; Organizational behavior; Social groups; Social service; Sinh thái xã hội; Tâm lý xã hội -- Hành vi con người